Prevalence and Outcomes of Pediatric In-Hospital Cardiac Arrest Associated With Pulmonary Hypertension*. Issue 4 (April 2020) - Morgan, Ryan W.; Topjian, Alexis A.; Wang, Yan; Atkin, Natalie J.; Kilbaugh, Todd J.; McGowan, Francis X.; Berg, Robert A.; Mercer-Rosa, Laura; Sutton, Robert M.; Himebauch, Adam S.
Abstract : Objectives: In adult in-hospital cardiac arrest, pulmonary hypertension is associated with worse outcomes, but pulmonary hypertension–associated in-hospital cardiac arrest has not been well studied in children. The objective of this study was to determine the prevalence of pulmonary hypertension among children with in-hospital cardiac arrest and its impact on outcomes. Design: Retrospective single-center cohort study. Setting: PICU of a quaternary care, academic children's hospital. Patients: Children (<18 yr old) receiving greater than or equal to 1 minute of cardiopulmonary resuscitation (cardiopulmonary resuscitation) for an index in-hospital cardiac arrest with an echocardiogram in the 48 hours preceding in-hospital cardiac arrest, excluding those with cyanotic congenital heart disease. Interventions: None. Measurements and Main Results: Of 284 in-hospital cardiac arrest subjects, 57 (20%) had evaluable echocardiograms, which were analyzed by a cardiologist blinded to patient characteristics. Pulmonary hypertension was present in 20 of 57 (35%); nine of 20 (45%) had no prior pulmonary hypertension history. Children with pulmonary hypertension had worse right ventricular systolic function, measured by fractional area change ( p = 0.005) and right ventricular global longitudinal strain ( p = 0.046); more right ventricular dilation ( p = 0.010); and better left ventricular systolic function ( p = 0.001). Children with pulmonary hypertension were more likely to have abnormal baseline functional status and a history of chronic lung disease or acyanotic congenital heart disease and less likely to have sepsis or acute kidney injury. Children with pulmonary hypertension were more likely to have an initial rhythm of pulseless electrical activity or asystole and were more frequently treated with inhaled nitric oxide (80% vs 32%; p < 0.001) at the time of cardiopulmonary resuscitation. On multivariable analysis, pulmonary hypertension was not associated with event survival (14/20 [70%] vs 24/37 [65%]; adjusted odds ratio, 1.30 [CI95, 0.25–6.69]; p = 0.77) or survival to discharge (8/20 [40%] vs 10/37 [27%]; adjusted odds ratio, 1.17 [CI95, 0.22–6.44]; p = 0.85). Conclusions: Pulmonary hypertension physiology preceding pediatric in-hospital cardiac arrest may be more common than previously described. Among this cohort with a high frequency of inhaled nitric oxide treatment during cardiopulmonary resuscitation, pulmonary hypertension was not associated with survival outcomes. Abstract : Supplemental Digital Content is available in the text.